El método Montessori y su incidencia en las relaciones socio emocionales de los niños de Educación Inicial - Narváez Hernández, Vanessa Yazmin (2022)
The present investigation focused on the study of the Montessori method and its impact on the socio-emotional relationships of children in Initial Education, it was developed in the Coronel Germánico Rivadeneira Valencia School of Basic Education in the Latacunga canton, in which the boys and girls, parents, teachers and Initial Education authorities. The problem lies in the little information and application that teachers have about the Montessori method, to be applied correctly in the socio-emotional processes of infants, which has prevented the development of empathy for others. For this reason, the general objective of the research was to determine the incidence of the Montessori method in the socio-emotional relationships of children in Initial Education. The methodology that has been used in the investigation has a quantitative-qualitative approach, the bibliographic and field design, not experimental, also for the acquisition of information the inductive method was used, which helped to clearly and precisely detail the characteristics and processes of the method. Montessori. The techniques used were the survey of parents, an interview with the teacher and the observation sheet for the children of Initial Education, which allowed the collection of information and data, which helped to support the research carried out, allowing to establish conclusions and final recommendations, the impact of the research was of a theoretical type since it supports the Montessori method and socio-emotional relationships in child development, in this way it is concluded that knowledge of the methodology of Maria Montessori is important, both caregivers and educators. They must be aware of the method, since the method has significant experiences for the development of the infant, promoting and strengthening socio-emotional relationships from early childh.